Translation and cross-cultural adaptation of the functional mobility scale in children with cerebral palsy into Arabic - Abdulaziz A. Albalwi; Maysoun N. Saleh; Maysoun N. Saleh; Ahmad A. Alharbi; Qais Al-Bakri; Salem F. Alatawi (Frontiers Media S.A., 2023)
IntroductionCerebral palsy (CP) is a lifelong disorder of posture and movement which often leads to a myriad of limitations in functional mobility. The Functional Mobility Scale (FMS) is a parent-report measure of functional mobility for children with CP at three different distances (5 m, 50 m, and 500 m). This is a cross-sectional study which sought to translate and culturally adapt the FMS into Arabic and to validate the translated version. Functional mobility for children and adolescents with CP in Saudi Arabia was examined.MethodsThe translation methodology complied with the World Health Organization Disability Assessment Schedule 2.0 translation package. A total of 154 children with CP were recruited (mean age 8.16 ± 3.32 years). Parents were interviewed to rate the usual walking ability of their children on the Arabic FMS. The re-test assessment was done with 34 families. The mean time interval between the first and second sessions was 14.3 days (SD = 8.5), with a range of 6-37 days.ResultsConcurrent validity was explored using Spearman's rank correlation coefficient between scores of the Arabic FMS with their corresponding score on the Gross Motor Function Classification System (GMFCS). Spearman's r values ranged between (−0.895 and -0.779), indicating strong to very strong correlations. The Test-retest reliability was examined using Cohen's weighted kappa, which showed almost perfect agreements. There was greater limitation for functional mobility at longer distances as 55.2% of children could not complete 500 meters (FMS score N). Overall, there was limited use of wheelchairs for all distances (ranging from 9.1% to 14.3%). Levels IV and V on the GMFCS had less variation in FMS scores and most of the children in these levels either did not complete the distances (no functional mobility at all distances) or used a wheelchair for mobility.DiscussionThe Arabic FMS was shown to be a reliable and valid measure of functional mobility for children with CP in their environment based on the parental reports. Functional mobility varied at different distances and within each GMFCS level. The use of both the GMFCS and FMS when assessing children with CP is recommended.